2018
DOI: 10.1371/journal.pone.0199347
|View full text |Cite
|
Sign up to set email alerts
|

Long-term use of carvedilol in patients with ST-segment elevation myocardial infarction treated with primary percutaneous coronary intervention

Abstract: BackgroundDespite its recommendation by the current guidelines, the role of long-term oral beta-blocker therapy has never been evaluated by randomized trials in uncomplicated ST-segment elevation myocardial infarction (STEMI) patients without heart failure, left ventricular dysfunction or ventricular arrhythmia who underwent primary percutaneous coronary intervention (PCI).Methods and resultsIn a multi-center, open-label, randomized controlled trial, STEMI patients with successful primary PCI within 24 hours f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 52 publications
(27 citation statements)
references
References 31 publications
2
23
0
2
Order By: Relevance
“…Indeed, in the CAPITAL-RCT trial, which is the only RCT exploring the effectiveness of an oral β-blocker in uncomplicated STEMI patients, the event rate for a composite of all-cause death, myocardial infarction, hospitalization for heart failure, and hospitalization for acute coronary syndrome at median 4-year follow-up was very low, and the event rate did not differ with regard to β-blocker use. 15 The lack of a dose-response relationship for β-blockers in the present study might be explained very well, if β-blockers are not at all effective in preventing cardiovascular events in patients with uncomplicated AMI. A large RCT (REDUCE-SWEDEHEART: ClinicalTrials.gov NCT 03278509) is ongoing to evaluate the role of β-blocker after AMI in contemporary practice.…”
Section: Editorialmentioning
confidence: 67%
“…Indeed, in the CAPITAL-RCT trial, which is the only RCT exploring the effectiveness of an oral β-blocker in uncomplicated STEMI patients, the event rate for a composite of all-cause death, myocardial infarction, hospitalization for heart failure, and hospitalization for acute coronary syndrome at median 4-year follow-up was very low, and the event rate did not differ with regard to β-blocker use. 15 The lack of a dose-response relationship for β-blockers in the present study might be explained very well, if β-blockers are not at all effective in preventing cardiovascular events in patients with uncomplicated AMI. A large RCT (REDUCE-SWEDEHEART: ClinicalTrials.gov NCT 03278509) is ongoing to evaluate the role of β-blocker after AMI in contemporary practice.…”
Section: Editorialmentioning
confidence: 67%
“…Убедительные данные об улучшении прогноза при назначении БАБ у больных с ОКСпST были получены, в основном, в дореперфузионную эру [156]. Польза рутинного назначе-ния БАБ у больных, которые подверглись первичной ЧКВ, на основании РКИ и системных мета-анализов, не показана [157,158,159,160]. Вместе с тем, результаты некоторых регистров говорят о том, что назначение БАБ приводит к улучшению прогноза [161,162].…”
Section: блокаторы бета-адренергических рецепторов (баб)unclassified
“…In the reperfusion era only one randomized controlled trial (CAPITAL-RCT) [12] has investigated the longterm efficacy of beta-blockers in patients with LVEF ≥ 40% after MI and successful PCI. The trial included patients with ST-elevation MI (STEMI) and suggested no benefit of carvedilol on a composite outcome (all-cause mortality, MI, hospitalization for HF and acute coronary syndrome) after a median follow up time of 3.9 years.…”
Section: Randomized Controlled Trials Evaluating Beta-blocker Therapymentioning
confidence: 99%
“…A metaanalysis of beta-blockers for HF with reduced, midrange, and preserved ejection fraction demonstrated no evidence of benefit of beta-blockers for all-cause mortality when LVEF was > 40% in sinus rhythm [48]. The ongoing trials DANBLOCK, BETAMI, and REBOOT and the published CAPITAL-RCT [12] all include patients with midrange LVEF. Hopefully, these trials will resolve whether beta-blockers are beneficial in this group of patients.…”
Section: Lvef Cutoff Valuementioning
confidence: 99%